2000
DOI: 10.5858/2000-124-1833-lmyarn
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Metastasis 7 Years After Radical Nephrectomy

Abstract: Metastasis of renal cell carcinoma to the head and neck, especially the larynx, is an extremely rare event. Most previously reported cases have involved a presenting laryngeal lesion that lead to the discovery of an underlying primary renal cell carcinoma. Even more unusual is the occurrence of an isolated laryngeal metastasis revealing itself years after nephrectomy, with an interim of undetected recurrence. We believe this case to be the first reported example of an isolated supraglottic laryngeal renal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This could be explained because most metastases to the larynx are through the systemic circulation, following the route of the inferior vena cava to the laryngeal artery, and through retrograde circulation of the paravertebral venous plexus or thoracic lymphatic duct10 and because the glottis and subglottis have fewer blood and lymphatic supply 11. In our case, the tumour was located to the glottis, and this has been described before only by a few articles 12–16…”
Section: Discussionmentioning
confidence: 57%
“…This could be explained because most metastases to the larynx are through the systemic circulation, following the route of the inferior vena cava to the laryngeal artery, and through retrograde circulation of the paravertebral venous plexus or thoracic lymphatic duct10 and because the glottis and subglottis have fewer blood and lymphatic supply 11. In our case, the tumour was located to the glottis, and this has been described before only by a few articles 12–16…”
Section: Discussionmentioning
confidence: 57%
“…Reviewing the literature we found eighteen reports of renal clear cell metastasis to the larynx. Most of those studies reported solitary metastasis to supraglottic region [9][10][11][12] , three of the studies reported solitary glottic metastasis [13][14][15] , three described Clear cell metastatic carcinoma of the larynx is an extremely rare diagnosis with low survival rate. While most patients in literature are treated with a combination of surgical and oncologic therapy, we present a case where prolonged survival was achieved in a patient who opted only for oncological treatment.…”
Section: Short Literature Reviewmentioning
confidence: 99%
“…The lungs, liver, bones, suprarenal glands, pleura, brain, and soft tissues are among the common sites of metastasis for RCC [ 2 ]. However, isolated RCC metastases to the head and neck region, particularly the larynx, are extremely rare [ 3 ].RCC is the second most common cancer to metastasize to the larynx after skin cancer [ 4 ], and secondary tumors of the larynx account for only 0.09% to 0.4% of all laryngeal tumors [ 5 ]. As a malignant disease, RCC is a great imitator with an erratic clinical course and biological behavior.…”
Section: Introductionmentioning
confidence: 99%